Perancangan Dan Implementasi Aplikasi Sistem Absensi Karyawan Berbasis Android Menggunakan Metode Agile Development - muhammad sulaiman; Yan Mitha Djaksana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In the early 2020, the world faces virus pandemic called corona virus. World Health Organization (WHO) states that people all over the world faced Covid-19. Afterwards, several countries announced global disaster, in march 2020, Indonesia decided to apply social distancing in big scale for avoiding the increase of people infected by corona virus. In Badan Wakaf Al-Quran institution, management is facing difficulty to get the employees working at home data to be the responsibility in converting the salary based on employees’ working hours. Therefore, the process of software development is based on software engineering that must be considered the structure and design. The software development model used in this study is the agile development method. Previously, the employees can only do the presence using conventional presence machine or using manual form. Therefore, mobile application based on android app is made to help Badan Wakaf Al-Quran to monitor the employees working at home. Agile development method is applied for building the application to ease the plan scheme into the building application step to get the necessary outcomes. The design and implementation of this mobile attendance application is limited to one of the modules, namely attendance. In the final stages of development, evaluation of the process and planning of software development.